The Circular RNA circRNA124534 Promotes Osteogenic Differentiation of Human Dental Pulp Stem Cells Through Modulation of the miR-496/β-Catenin Pathway - Ji, Fang; Pan, Jing; Shen, Zhecheng; Yang, Zhao; Wang, Jian; Bai, Xuebing; Tao, Jiang (Frontiers in Cell and Developmental Biology, 2020)
Circular RNAs (circRNAs) have been found to be a crucial role in stem cell-associated bone regeneration. However, the functions and underlying mechanisms of circRNAs in the osteogenic differentiation of human dental pulp stem cells (hDPSCs) remain largely unclear. We found that overexpression of circRNA124534 unexpectedly promoted DPSCs osteogenesis in vitro and in vivo. Our results confirmed circRNA124534, acting as a miRNA sponge, directly interacts with miR-496 and consequently regulates β-catenin, which in turn exerts osteogenesis of DPSCs. Enforced expression of miR-496 reversed the osteogenesis of circRNA124534, and suppression of miR-496 enhanced the osteogenic differentiation of DPSCs by promoting β-catenin. In conclusion, our findings demonstrate functions of circRNA124534 in modulating osteogenic differentiation through the miR-496/β-catenin pathway; thus, providing a novel potential target for therapy.